Strategi Inovatif Pembelajaran Mendalam : Upaya Meningkatkan Kompetensi Guru Sekolah Dasar - Nurhidayati Nurhidayati; Rintis Rizkia Pangestika; Joko Purwanto; Ilham Samsul Hadi; Ranti Dwi Cahyani (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Deep learning (immersion learning) focuses on understanding concepts and developing critical thinking skills. However, 65% of elementary school teachers in partner schools still have difficulty implementing it. The purpose of this article is to identify innovative strategies to improve teacher skills through training 65 teachers from 8 elementary schools who are members of the teacher working group. The results of the training showed that 80% of teachers improved understanding, 70% reported increased interactive learning, and 60% used learning techniques. Continuous training and support in the use of technology are essential to enrich the learning experience for students. It is expected to inspire education policies at the elementary school level to optimize the implementation of deep learning in competency-based curriculum and improve the quality of education.